2020
DOI: 10.1017/ice.2020.301
|View full text |Cite
|
Sign up to set email alerts
|

Widespread severe acute respiratory coronavirus virus 2 (SARS-CoV-2) laboratory surveillance program to minimize asymptomatic transmission in high-risk inpatient and congregate living settings

Abstract: We describe a widespread laboratory surveillance program for severe acute respiratory coronavirus virus 2 (SARS-CoV-2) at an integrated medical campus that includes a tertiary-care center, a skilled nursing facility, a rehabilitation treatment center, and temporary shelter units. We identified 22 asymptomatic cases of SARS-CoV-2 and implemented infection control measures to prevent SARS-CoV-2 transmission in congregate settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…The studies were all observational in nature. [ [11] , [12] , [13] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] ] All of the studies reported RT-PCR-confirmed COVID-19 cases amongst the residents.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The studies were all observational in nature. [ [11] , [12] , [13] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] ] All of the studies reported RT-PCR-confirmed COVID-19 cases amongst the residents.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…A number of included studies reported infection attack rates of SARS-CoV-2 among study participants: 29 studies measured positivity rates (i.e., current infection) [ 13 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], seven measured seroprevalence (i.e., prevalence of antibodies for SARS-CoV-2, indicating historic infection) [ 61 , 62 , 63 , 64 , 65 , 66 , 67 ], and four measured both positivity and seroprevalence rates [ 68 , 69 , 70 , 71 ]. Additionally, data regarding SARS-CoV-2 symptoms reported by study participants were provided by 32 articles [ 7 , 8 , 33 , 34 , 35 , 36 , 38 , 42 , 45 , 46 , …”
Section: Resultsmentioning
confidence: 99%
“…In terms of IPC strategies, 11 studies [29,31,35,37,39,42,47,48,54,56,57] discussed comprehensive and rapid testing including collaboration with regional laboratories for quick turnaround of positive tests, expansion of non-congregate housing and individual strategies in the shelters, e.g. spacing between beds and limited staff rotation, as critical measures to be taken.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Jatt et al [29], described that the implementation of a widespread surveillance testing strategy has likely prevented asymptomatic transmission of SARS-CoV-2, thereby preventing potential outbreaks of Covid-19 in their study, which included 121 homeless (out of 1781 participants), at an integrated medical campus with tertiary-care center, skilled nursing facility, rehabilitation treatment center, and temporary shelter units.…”
Section: Infection Protection and Control (Ipc) Strategies In Homeless Sheltersmentioning
confidence: 96%
See 1 more Smart Citation